2017
DOI: 10.1016/j.ajme.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk assessment by Gail Model in women of Baghdad

Abstract: Objectives: To assess the high incidence of breast cancer (BC) and the effect of its early diagnosis on decreasing morbidity and mortality among Iraqi women. Methods: A descriptive cross-sectional study was conducted and data were collected from 250 women in Baghdad by a questionnaire consisted of demographic and breast cancer risk (BCR) factors questions. Brest cancer risk was calculated using the BCR Assessment Tool (BCRAT) of the National Cancer Institute's online version (Gail Model). Results: The average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…In our findings, the mean score of 5-year calculated breast cancer risk was 0.98 percent according to the Gail model that is similar to those reported from our neighborhood country among the Turkish and Iraqi women with an average 5-year risk of 0.88 and 0.95 percent respectively 27,28. Our calculated 5-year risk by the Gail model is rather similar to other studies of Iranian women where the average 5-year risk of 0.76 percent was reported 29,30.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our findings, the mean score of 5-year calculated breast cancer risk was 0.98 percent according to the Gail model that is similar to those reported from our neighborhood country among the Turkish and Iraqi women with an average 5-year risk of 0.88 and 0.95 percent respectively 27,28. Our calculated 5-year risk by the Gail model is rather similar to other studies of Iranian women where the average 5-year risk of 0.76 percent was reported 29,30.…”
Section: Discussionsupporting
confidence: 89%
“…The Gail model has been validated in breast cancer risk prediction in different populations and it is generally accurate in risk projection 2528. However, some overestimation of the likelihood of risk may occur in a specific subgroup (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The original model was derived from general American white women with annual mammography screening 12 , 17 and hence, it can be suitable for populations such as in the current study and other similar studies. 13 - 15 , 20 Nevertheless, one of the important limitations of Gail model is the lack of consideration of breast cancer among second degree-relatives as a risk factor. Furthermore, a number of previous studies have shown that the Gail model may overestimate the risk of development of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 7 - 11 Among the widely available risk assessment models for breast cancer, Gail model remains the most frequently used tool for prediction of the 5-year and lifetime risks of developing breast cancer for women aged 35 years and older. 12 - 15 It uses 6 breast cancer risk factors, including age, hormonal or reproductive history (age at menarche and age at first live birth), previous history of breast disease (number of breast biopsies and history of atypical hyperplasia), and family history (number of first-degree relatives with breast cancer).…”
Section: Introductionmentioning
confidence: 99%
“…The data obtained were analyzed and ranked on the basis of informant concensus factor (ICF), fidelity Level (FL), use value (UV) and relative frequency The recorded use reports data have been classified to different types of cancer (Table 2). The highest ICF (0.93) was registered for breast cancer, followed by ovarian cancer (0.81), which could be due to the increased prevalence of these two types of cancer worldwide but also in Morocco [27].…”
Section: Ethnobotanical Indicesmentioning
confidence: 95%